2012
DOI: 10.3109/09638288.2012.691939
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression after stroke: a 5 year follow-up

Abstract: Anxiety and depression were more frequent at 5 years after stroke than at 6 months. There were significant differences between four European centres in the severity of anxiety and depression. Although the main determinant of anxiety or depression scores at 5 years was the level of anxiety or depression at 6 months, this accounted for little of the variance. Centre was also a significant predictor of mood at 5 years. There needs to be greater recognition of the development of mood disorders late after stroke an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 23 publications
5
78
0
9
Order By: Relevance
“…A seminal 1993 study in 309 consecutive acute stroke patients found that 27% had GAD according to DSM-III-R criteria [3]. Longitudinal studies indicate that GAD prevalence remains high up to 5 years after stroke [4][5][6]. A recent review of 44 post-stroke studies reported pooled prevalence of 18% when anxiety was assessed by clinical interview and 25% when assessed by rating scale [7].…”
mentioning
confidence: 96%
“…A seminal 1993 study in 309 consecutive acute stroke patients found that 27% had GAD according to DSM-III-R criteria [3]. Longitudinal studies indicate that GAD prevalence remains high up to 5 years after stroke [4][5][6]. A recent review of 44 post-stroke studies reported pooled prevalence of 18% when anxiety was assessed by clinical interview and 25% when assessed by rating scale [7].…”
mentioning
confidence: 96%
“…Almost half of those over the age of 75 years had problems with anxiety or depression. Previous studies have shown that older stroke patients are more likely to experience depression, [165,166] even among those who are considered to have recovered fully physically [164].…”
Section: Discussionmentioning
confidence: 99%
“…Hackett und Kollegen [34] zeigen in ihrem Review auf, dass etwa ein Drittel aller Überlebenden eines Schlaganfalls im Verlauf eine Depression entwickelt. Diese Aussage wird gestützt durch eine aktuelle 5-JahresFollow-up-Studie der Forschergruppe um Lincoln [35]. Die psychosozialen Folgen einer Aphasie verstärken sich mit zunehmendem Alter [9].…”
Section: Das Problem Und Die Folgen Für Die Betroffenenunclassified